The Preservation and Adaptation of Betang Culture in Central Borneo in the Era of Globalization - Mau, Daniel Pandu; Mau, Yesarela Pandu; Kurniansah, Rizal; Ariawan, I Wayan Adi Putra (Universitas Tanjungpura, 2024)
The purpose of the research was to examine the Dayak community in Central Kalimantan, aiming to explore the impact of globalization on the traditional values of Betang that reflect their social, legal, and economic structures. The methodology employed an ethnographic approach, utilizing participatory observation and in-depth interviews with customary leaders, youth, and local officials. The findings indicated that the Betang serves not only as a communal house but also embodies a complex social system characterized by values of togetherness, honesty, and egalitarianism. The Dayak community practiced the principles of hapahari (brotherhood) and handep (mutual cooperation) as central to their social interactions and conflict resolution, while also upholding customary laws. Furthermore, the cooperative-based system facilitated equitable resource management. In conclusion, despite influences from modernization, the values associated with Betang remained fundamental to the lives of the Dayak people, showcasing their ability to balance cultural preservation with adaptation to change. The research underscores the importance of preserving traditional values in rapid social change, highlighting that such preservation is essential for maintaining cultural identity, especially in the evolving era of globalization.